A new technique for seprafilm® that can be practiced with a 5-mm trocar - Rikiya Sano; Yoshiaki Ota; Tamaki Tanaka; Soichiro Suzuki; Koichiro Shimoya; Mitsuru Shiota (Wolters Kluwer Medknow Publications, 2021)
Seprafilm® is an adhesion barrier sheet. However, it is difficult to handle it through a 5-mm trocar. We have devised a method of applying Seprafilm® safely and reliably through a 5-mm trocar by using a holder that comes with the film. We practiced this method in three cases of total laparoscopic hysterectomy for uterine leiomyoma. The quarter-pack is cut into three pieces. The film placed on the holder sheet was rolled up with forceps (or wrapped around forceps) and inserted into a 5 mm trocar. After application, the center of the short axis of the holder was pinched with a grasping forceps, and the holder was drawn out of the body through the trocar. Of the 36 pieces placed, Seprafilm® broke only in once. Insertion was successful in 100%, and the holder was successfully retrieved through the trocar in 92% (33/36) of the cases. The holder may be easily retrieved after application. This technique represents an extremely simple versatile application method in operations in which only 5-mm trocars can be used.